Plasmodium berghei Cap93, a novel oocyst capsule-associated protein, plays a role in sporozoite development - Hanae Sasaki; Harumi Sekiguchi; Makoto Sugiyama; Hiromi Ikadai (Parasites & Vectors, 2017)
Abstract Background Disruption of Plasmodium oocyst capsule protein (PbCap380), and an oocyst wall interior protein, circumsporozoite protein, results in sporozoites not being formed, despite the formation of oocysts, and prevents malaria transmission. Therefore, these key oocyst capsule-associated proteins are responsible for the development of the oocyst capsule and play an important role in the later growth and maintenance of sporozoites. We attempted to discover novel oocyst capsule-associated proteins and analyze their functions by assuming that such proteins will be strategically important targets for preventing malaria transmission. A putative, novel oocyst capsule-associated protein, known as PbCap93, was determined from the PlasmoDB database, and we aimed to create a knockout parasite of the PbCap93 gene to analyze its functions in the mosquito stage. Results To investigate the kinetics of PbCap93 protein expression, we labelled the asexual stage and mosquito stage parasites with anti-PbCap93 antibodies using IFAT. PbCap93 was detected in oocysts on day 15 after infection, though it was not detected in sporozoites of ruptured oocysts. PbCap93 localizes interior to the oocyst capsule alone without localization to the sporozoite plasma membrane. To gain further insight regarding PbCap93 function, we disrupted the gene in P. berghei parasites. Between 14 and 15 days after receiving a parasite-laden blood meal, 100 midguts were dissected from mosquitoes that received either wild-type (WT) or knocked out (KO) parasites. For WT parasites, the oocyst infection rate was 50%, whereas, for KO parasites, the infection rate was 16.7%. The average number of oocysts per midgut was 12 for the WT parasites compared with 0.8 for the KO parasites. Furthermore, KO parasite oocysts were significantly smaller than WT parasite oocytes. Using transmission electron microscopy, we observed that the electron density of the PbCap93-KO oocyst capsule was lower than that of the WT oocyte capsule. Conclusions We posited that the PbCap93 protein is secreted from sporoblasts within the oocysts until sporozoites are formed. PbCap93 constructs the interior of the oocyst capsule or part of the plasma membrane and affects sporozoite differentiation. Further studies are warranted to understand the mechanism of oocyst formation.